Changes to Gestational Diabetes Mellitus (GDM) Testing and Associations with the GDM Prevalence and Large- and Small-for-Gestational-Age Infants—An Observational Study in an Australian Jurisdiction, 2012–2019 - Jennifer Hutchinson; Catherine R. Knight-Agarwal; Christopher J. Nolan; Deborah Davis (Diabetology)
Background: Two changes to gestational diabetes mellitus (GDM) testing were implemented in the Australian Capital Territory in 2015 and 2017. Aims: We aimed to determine the associations between testing regimes and the prevalence of GDM and large-for-gestational-age (LGA) and small-for-gestational-age (SGA) infants and to compare the prevalence of LGA and SGA infants between women with and without GDM in each testing period. Methods: A total of 23,790 singleton live births with estimated GDM testing and birth dates between June 2012 and December 2019 were stratified into groups: pre-testing changes (June 2012–December 2014, group 1, n = 8069), revised diagnostic criteria (January 2015–May 2017, group 2, n = 8035) and changed pathology centrifugation protocol (June 2017-December 2019, group 3, n = 7686). Women were allocated to groups based on their estimated GDM testing date and stratified by their GDM status. A chi-square test, pairwise z-tests and logistic regression tested the associations. Results: The GDM prevalence significantly increased from 9.5% (group 1) to 19.4% (group 2) to 26.3% (group 3) (all: p < 0.001). The LGA infant prevalence significantly decreased in non-GDM women following revised diagnostic criteria implementation (11.6% vs. 9.7%, p = 0.001). Compared to group 1, women with GDM in groups 2 and 3 had significantly reduced odds of having LGA infants (aOR = 0.73, 95% CI of 0.56–0.95 and p = 0.021 and aOR = 0.75, 95% CI of 0.59–0.97 and p = 0.029, respectively). Compared to group 1, non-GDM women in groups 2 and 3 had significantly reduced odds of having LGA infants (aOR = 0.83, 95% CI of 0.74–0.92 and p < 0.001 and aOR = 0.88, 95% CI of 0.79–0.99 and p = 0.026, respectively). There were no significant associations for group 3 compared to group 2 nor for SGA infants. Conclusions: While significantly increasing the GDM prevalence, implementing the testing changes was associated with a reduced whole-population LGA infant prevalence without a change in the SGA infant prevalence.